1997
DOI: 10.1002/(sici)1097-0304(199704)40:4<364::aid-ccd9>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial infarction associated with myocardial bridging: Case history and review of the literature

Abstract: Myocardial infarction may occur without atherosclerotic lesions discernible by coronary angiography. The impact of this phenomenon may not be appreciated by many clinicians largely because of a priori assumptions that patients who present with a history of MI or angina syndrome are victims of atherosclerosis and fit well into mainstream management ranging from acute care to rehabilitation. In the absence of atherosclerosis, myocardial infarction may result from several etiologies by chronic hypoperfusion if th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(70 citation statements)
references
References 52 publications
0
68
0
1
Order By: Relevance
“…Some case reports have indicated that a relationship exists between MB and major cardiac events, such as myocardial infarction [12][13][14][15][16][17] and cardiac sudden death. [18][19][20][21] Several factors may account for MB-related myocardial ischemia.…”
Section: Cardiac Events Associated With Myocardial Bridgingmentioning
confidence: 99%
See 1 more Smart Citation
“…Some case reports have indicated that a relationship exists between MB and major cardiac events, such as myocardial infarction [12][13][14][15][16][17] and cardiac sudden death. [18][19][20][21] Several factors may account for MB-related myocardial ischemia.…”
Section: Cardiac Events Associated With Myocardial Bridgingmentioning
confidence: 99%
“…[1][2][3] The frequency of MB has been reported to range from 5.4 to 85% in autopsy series [4][5][6] and from 0.5 to 29.4% on coronary angiography. 1,[6][7][8][9][10][11] Although it remains to be determined how MB affects the cardiovascular system, MB has been associated with myocardial infarction [12][13][14][15][16][17] and sudden cardiac death, [18][19][20][21] and coronary spasm is thought to be one factor connecting cardiac events and MB. 13,22,23 However, it has yet to be verified that coronary spasm is more frequent in patients with MB.…”
Section: Introductionmentioning
confidence: 99%
“…It has been well established the association between MB and complications such as ischemia and acute coronary syndrome 19 , reported by 56% of the studied patients; AMI 20 affecting 40% of the patients and sudden death 21 , which was the cause of death of one patient in the present study. Other complications are: coronary spasm 22 ; ventricular septum rupture 23 , supraventricular paroxysmal tachycardia 24 ; ventricular tachycardia 25 and exercise-induced atrioventricular block 26 , which were not reported by the patients in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a portion of the vesel under the "bridge" of contractile myocardium repeatedly results in arterial compression during each systole. While frequently asymptomatic, this condition in many cases may be guilty of adverse events including angina, myocardial ischemia [3], acute coronary syndromes [4][5][6], left ventricular dysfunction and stunning [7], arrhythmias [8,9], and even sudden cardiac death [10,11]. Described rates of myocardial bridging vary based on the mode of evaluation.…”
Section: Introductionmentioning
confidence: 99%